Microbiome Profiling Reveals Gut Dysbiosis in the Metabotropic Glutamate Receptor 5 Knockout Mouse Model of Schizophrenia - Gubert, Carolina; Kong, Geraldine; Uzungil, Volkan; Zeleznikow-Johnston, Ariel M.; Burrows, Emma L.; Renoir, Thibault; Hannan, Anthony J. (Frontiers in Cell and Developmental Biology, 2020)
Schizophrenia (SZ) is a psychiatric disorder that constitutes one of the top 10 global causes of disability. More recently a potential pathogenic role for the gut microbial community (microbiota) has been highlighted. However, no animal model of SZ has previously recapitulated the gut dysbiosis observed clinically. The metabotropic glutamate receptor 5 (mGlu5) knockout mice provide a preclinical model of SZ with strong face and predictive validity. In the present study we performed gut microbiome profiling of mGlu5 knockout (KO) and wild-type (WT) mice by 16S rRNA sequencing of bacterial genomic DNA from fecal samples, analysing bacterial diversity and taxonomic composition. We found a significant genotype difference in microbial beta diversity. Analysis of composition of microbiomes (ANCOM) models were performed to evaluate microbiota constituents, which identified a decreased relative abundance of Erysipelotrichaceae family and Allobaculum genus in this mouse model of SZ. We also identified a signature of bacteria discriminating between the genotypes (KO and WT), consisting of the Erysipelotrichales, Bacteroidales and Clostridiales orders. We thus uncovered global differential community composition in the gut microbiota profile between mGlu5 KO and WT mice, outlining the first evidence for gut dysbiosis in a genetic animal model of SZ. Our findings suggest that this preclinical model of SZ also has substantial utility to investigate gut dysbiosis and the microbiota-gut-brain axis, as modulators of SZ pathogenesis. Our discovery opens up new avenues to explore gut dysbiosis and its proposed links to brain dysfunction in SZ, as well as novel therapeutic approaches for this devastating disorder.